Significant performance improvement in dye-sensitized solar cells employing cobalt(iii/ii) tris-bipyridyl redox mediators by co-grafting alkyl phosphonic acids with a ruthenium sensitizer - Liu, Y. (2014)
10.1039/c3cp50998b